2020
DOI: 10.1101/2020.12.21.423738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inclusion of maintenance energy improves the intracellular flux predictions of CHO

Abstract: Chinese hamster ovary (CHO) cells are the leading platform for the production of biopharmaceuticals with human-like glycosylation. The standard practice for cell line generation relies on trial and error approaches such as adaptive evolution and high-throughput screening, which typically take several months. Metabolic modeling could aid in designing better producer cell lines and thus shorten development times. The genome-scale metabolic model (GSMM) of CHO can accurately predict growth rates. However, in orde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Firstly, it may be a result of the use of a generic biomass equation, which did not effectively capture the true biomass composition of cells resulting in an underprediction of fluxes. It may also be due to the lack of an ATP maintenance constraint, which has been shown to improve intracellular flux predictions (Széliová, Štor, et al, 2020 ). Finally, it may be indicative of the “metabolic efficiency” of these models compared to in vivo metabolism, meaning lower flux values through core reactions are able to satisfy the model constraints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, it may be a result of the use of a generic biomass equation, which did not effectively capture the true biomass composition of cells resulting in an underprediction of fluxes. It may also be due to the lack of an ATP maintenance constraint, which has been shown to improve intracellular flux predictions (Széliová, Štor, et al, 2020 ). Finally, it may be indicative of the “metabolic efficiency” of these models compared to in vivo metabolism, meaning lower flux values through core reactions are able to satisfy the model constraints.…”
Section: Resultsmentioning
confidence: 99%
“…To compare CHO cell model predictions with experimental flux data, the 13 C‐labeled reactions were mapped to the reactions in our metabolic models. The draft mapping was modified from Széliová, Štor, et al ( 2020 ) and is available in Supporting Information: Table S4 . One‐to‐one mapping was not possible for most reactions as the 13 C‐labeling lumped several reactions into one.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Löffler et al (2016) showed that several fluxes exist in the ATP supply inside the cell that is not related to cell growth. The study of Széliová et al (2021) on CHO cells showed that minimizing the absorption of nonessential nutrients is similar to maximizing growth and that the idea of minimizing fluxes and their sum in pFBA is the same as that of cells attempting to maximize resource utilization. Chen et al (2019) found that amino acid consumption estimated by the “minimization of essential nutrients” method is more accurate and demonstrated that minimization of non‐essential nutrient intake is more appropriate for CHO 's modeling objectives.…”
Section: Discussionmentioning
confidence: 99%
“…When Kadir et al (2010) combined these data, they found that ATP production and dilution rates had a linear relationship, with a slope of approximately 250. Széliová et al (2021) predicted the flux of maintenance in CHO cells, and also provided the total ATP production of CHO at different growth rates. The current work also found that the slope of the specific growth rate and ATP yield is approximately 180.…”
Section: Discussionmentioning
confidence: 99%